The 19th century restoration of Sansovino’s Loggetta in Piazza San Marco - Giulio Lupo (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
Between 1876 and 1885 a restoration was carried out at Sansovino’s Loggetta in Piazza San Marco. The documentary material is of some interest. First of all, it offers new information on the building and new reasons for reflecting on the original state of the Loggetta and, above all, it records a significant theoretcical change in the culture of restoration towards conservation, imprinted by the Ministry of Education with the ministerial decree and related circular dated 1882, July, 21st. Following the new principle of Conservation, Camillo Boito, sent to Venice by the Ministry in Rome, was legitimized to have all the columns of the recently restored main façade taken down, and put back out of plumb, as they were before the restoration.